CULTURAL ENGAGEMENT THROUGH E-MODULES: THE DEVELOPMENT OF LOCAL WISDOM BASED MATERIAL TO IMPROVE HIGH SCHOOL STUDENTS’ READING COMPREHENSION SKILLS IN ACEH - Intan Zuhra; Muhammad Alfata; Mutia Agustisa; Muhammad Darwis; Muhammad Haris Mustaqim (Universitas Muhammadiyah Metro, 2026)
A narrative text E-Module based on Acehnese local wisdom has never been developed by any scholars, yet it is essential for material development in English as a Foreign Language (EFL) context at high school level to enhance students’ reading comprehension skills. The research process involved four stages: needs analysis, expert validation, implementation, and student response evaluation. The needs analysis involving 35 students revealed that learners required short, simple, accessible, and up-to-date texts, particularly folklores reflecting local wisdom. Expert validation indicated that the developed E-Module achieved a “very validâ€ category, with material validation scoring 96.7% and media validation scoring 94.6%. While the module was considered highly effective in improving vocabulary, inference, and comprehension skills, experts recommended minor revisions to better support independent learning and enrich multimedia features. The effectiveness of the E-Module was further confirmed through a paired sample t-test, which demonstrated a significant improvement between pre-test and post-test scores (t = -10.81, p < 0.05), with a mean gain of 26.57 points. Moreover, students’ responses were overwhelmingly positive, with 80%–89% strongly agreeing and 6%–14% agreeing across aspects such as ease of use, systematic arrangement, motivation, and contribution to reading comprehension. This study concludes that the developed E-Module is pedagogically sound, contextually relevant, and feasible for broader implementation in EFL reading instruction. This study provided reading material with local wisdom based that can be easily access online.